Employee Engagement Among Generation Z in Tourism Business: The Role of Technology, Organizational Culture, and Servant Leadership - Kristiana, Yustisia; Nathalia, Theodosia C.; Goeltom, Vasco A. H. (Politeknik Pariwisata Makassar, Indonesia, 2025)
Employee engagement among Generation Z in tourism businesses is essential as they enter the workforce. This study examines how information technology utilization, organizational culture, and servant leadership influence employee engagement among Generation Z in Jakarta's tourism sector. It also explores the mediating role of servant leadership in these relationships. Using a quantitative approach, data were collected from 200 respondents through purposive sampling. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that information technology utilization, organizational culture, and servant leadership positively impact employee engagement. Additionally, servant leadership mediates the relationship between information technology utilization, organizational culture, and employee engagement. This study contributes to employee engagement theory by emphasizing the psychological conditions necessary for full engagement. It also underscores servant leadership's role in fostering psychological safety through support, empowerment, and ethical guidance. From a practical perspective, the findings highlight the need for tourism businesses to leverage technology, build a strong organizational culture, and adopt servant leadership practices that align with Generation Z’s expectations to enhance engagement.